Risco tecnológico e socioambiental na proposta de CDS (City Development Strategies) do banco mundial - Fujita, Camila (2003)
This research report focuses on the relationships among the society, the technology and the environment under the debate of risk, in order to weave considerations concerning to the importance of the discursive construction of the information and the control over the diffusion means of risk interpretations by hegemonic agents. By means of historical, social, cultural, scientific and educational approaches, the research conforms a view which takes the assumption that the risk notions are the result of social and historical constructions. Those constructions are strongly influenced by the technical and scientific approach, which nowadays plays an important role in the symbolic struggle for the democratization of the power over the techniques. The work intends to verify what kind of risk notion is elaborated in the proposals of CDS (City Development Strategies) produced by the World Bank and how those conceptions function to legitimate the intervention of the Bank. Through the accomplishment of a documental interpretative analysis which was confronted with the formulated theoretical mark, it was verified that the World Bank´s speech sees the local social actors as the responsible ones for the generation of the social problems. In order to do só, it asserts the non technical competence of local actors associated with the utilitarian notion of risk. However, at the same time, the Bank doesn’t evaluate the influence that the implementation of its own politics causes in the propagation of an excluding and hierarchical economical and ideological model, which worsens the urban reality of poor countries more and more.